Tourism, financialization, and short-term rentals: the political economy of Dublin's housing crisis. Issue 20 (18th October 2022) - Clancy, Michael
ABSTRACT: The impact of short-term rentals (STRs) such as Airbnb on housing markets has been of increasing concern to scholars, policy makers and housing advocates. Yet they do not take place in a vacuum. This article examines the political economy of STRs – and their relationship to the broader housing crisis – in Dublin, Ireland. The aim is to contribute in two ways: First is to provide another case study of STR platforms such as Airbnb on urban housing markets. Dublin is a useful case study in that it represents a major tourism destination and one where the government has continued to pursue international tourists as an economic development strategy. Second is to argue that these studies need to examine the larger context of housing policy as well as other factors that make housing markets in several places so tight in the first place. Here each story is different and is the product of a mixture of government policies, the broader political economy of the country, and global political economy factors such as TNC strategies and financialization. The article places STRs within this broader framework but also shows their localized effects through mapping Airbnb penetration in specific neighbourhoods in Dublin.